Attrition in the Austrian generations and gender survey - Isabella Buber-Ennser (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
In longitudinal research, the loss of sample members between waves is a possible source of bias. It is therefore crucial to analyse attrition and to find out who remained in the sample. The current paper analyses attrition in the Austrian Generations and Gender Survey, a longitudinal study on family and fertility, by distinguishing between attrition due to non-contact and attrition due to cooperation. The two components of attrition are studied separately by using bivariate as well as multivariate methods. Moreover, overall dropout - the combination of both components - is analysed. Apart from various socio-economic characteristics and data collection information, the study focuses on fertility relevant variables such as fecundity, fertility intentions, sexual orientation and traditional attitudes. The results reveal that fecundity, fertility intentions and homosexual relationship are associated with higher attrition due to refusal in bivariate analyses but have no explanatory power in the multivariate model. On the contrary, pregnancy and traditional attidudes towards marriage are significantly associated with lower attrition due to refusal in the multivariate context. Moreover, various individual and regional characteristics turned out to be significantly associated with dropout, with differences between attrition due to non-contact and attrition due to cooperation.
Keywords: 300; attrition; dropout; response rate; generations and gender survey; longitudinal data; Austria